Visual memory in offspring of parents with mental illness. (April 2020) - Howes Vallis, Emily; MacKenzie, Lynn E; Rempel, Sheri; Stephens, Meg; Howard, Cynthia; Drobinin, Vladislav; Propper, Lukas; Omisade, Antonina; Pavlova, Barbara; Uher, Rudolf
Highlights: Lower cognitive performance may be a risk factor for future severe mental illness. Visual memory is a potential cognitive predictor of risk for mental illness. Severe parental illness is associated with lower offspring visual memory ability. Abstract: Severe mental illness (SMI) refers to impairing and frequently chronic disorders that are difficult to treat. Lower cognitive performance early in life may be a manifestation of risk for SMI. Visual memory has been highlighted as a potential cognitive predictor of future risk of developing bipolar disorder and schizophrenia. We examined visual memory in 214 participants (mean age = 12.62, SD = 4.49) using the Rey Complex Figure Test (RCFT). Our sample included 37 offspring with no parental history of mental illness, 103 offspring with parental history of non-severe mental illness (NSMI), and 74 offspring with parental history of SMI. We tested the effects of family history of mental illness on visual memory using mixed-effects linear regression. After accounting for age, sex, and family clustering, we found that as severity of parental mental illness increases, offspring visual memory performance decreases significantly ( b = -3.58, 95% CI -6.79 to -0.37, p = 0.029). We found that severity of parental mental illness predicts visual memory ability. This finding may help identify youth most at risk of developing mental illness and thus inform future interventions.